Advanced mathematics for engineers and scientists - Spiegel, Murray R. (New York : McGraw-Hill, 1971)
A classic Schaum's Outline, now in the handsome new series cover design. The ideal review for the thousands of students who enroll in advanced mathematics courses.
1. Review of Fundamental Concepts 2. Ordinary Differential Equations 3. Linear Differential Equations 4. LaPlace Transforms 5. Vector Analysis 6. Multiple Line and Surface Integrals and Integral Theorems 7. Fourier Series 8. Fourier Integrals 9. Partial Differential Equations 10. Complex Variables and Conformal Mapping 11. Complex Inversion Formula for Laplace Transforms 12. Matrices 13. Calculus of Variations
Includes index.
1
Keywords: Engineering mathematics -- Outlines, syllabi, etc; Engineering mathematics -- Problems, exercises, etc